The contribution of complicity - Dyson, M (SAGE Publications, 2022)
Complicity provides a perfect place from which to take steps towards a doctrinally clear and coherent criminal law. In particular, by acknowledging in the complex mass of cases a requirement that the accomplice contribute to the principal's crime. That takes effect differently in assistance and encouragement compared to procuring: (a) an accessory's assistance or encouragement must make a significant contribution to the principal's crime, but does not need to be a but-for cause, and (b) to procure an offence, an accessory must cause it in a but-for sense. This requirement flows from how complicity can be justified and determines the linguistic form of complicity. It extends to the end point of complicity: overwhelming supervening events and withdrawal on the one hand, and sentencing on the other. Fidelity to how we express, and label, the wrongs within participation are important parts of the work we expect it to do. That includes what the wrong in complicity is (and how participants are labelled), the limits in what one can do through another or intend another can do, the causal claims we make in complicity and the differences between forms of complicity. Without even a significant contribution, an accomplice is not meaningfully involved in the principal's crime.